Pemanfaatan Limbah Serbuk Kayu Sebagai Subtitusi Agregat Halus Pada Beton - Loryanti Elsandi Paranggai; Junus Mara; Lisa Febriani (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
Concrete is the most widely used material as the main material in construction. As time progresses, human needs also increase, so in this study, wood waste was used into concrete mix with a normal concrete compressive strength value of 20 MPa using aggregate from the Jeneberang River. In this study, using sawdust waste to be utilized in concrete with variations of 0%, 3%, 6% and 9% with the aim of research to find out how the effect of sawdust waste into concrete mix with predetermined variations. The implementation method uses the SNI method by making test objects in the form of cylinders and blocks at the Indonesian Christian University Paul Laboratory. From the results of the research conducted, it was found that the effect of sawdust waste mixed into the concrete mixture showed the value of the compressive strength, tensile strength and flexural strength of the concrete increased by 3% then decreased in variations of 6% and 9% but at the addition of 3% the strength value The compressive strength, tensile strength and flexural strength of concrete decreased compared to normal concrete.